Development and characterization of a non-human primate model of disseminated synucleinopathy - Rico, Alberto J.; Corcho, Almudena; Chocarro, Julia; Ariznabarreta, Goiaz; Roda, Elvira; Honrubia, Adriana; Arnaiz, Patricia; Lanciego, José L. (Frontiers in Neuroanatomy, 2024)
Introduction The presence of a widespread cortical synucleinopathy is the main neuropathological hallmark underlying clinical entities such as Parkinson’s disease with dementia (PDD) and dementia with Lewy bodies (DLB). There currently is a pressing need for the development of non-human primate (NHPs) models of PDD and DLB to further overcome existing limitations in drug discovery. Methods Here we took advantage of a retrogradely-spreading adeno-associated viral vector serotype 9 coding for the alpha-synuclein A53T mutated gene (AAV9-SynA53T) to induce a widespread synucleinopathy of cortical and subcortical territories innervating the putamen. Four weeks post-AAV deliveries animals were sacrificed and a comprehensive biodistribution study was conducted, comprising the quantification of neurons expressing alpha-synuclein, rostrocaudal distribution and their specific location. Results Intraputaminal deliveries of AAV9-SynA53T lead to a disseminated synucleinopathy throughout ipsi- and contralateral cerebral cortices, together with transduced neurons located in the ipsilateral caudal intralaminar nuclei and in the substantia nigra pars compacta (leading to thalamostriatal and nigrostriatal projections, respectively). Cortical afferent systems were found to be the main contributors to putaminal afferents (superior frontal and precentral gyri in particular). Discussion Obtained data extends current models of synucleinopathies in NHPs, providing a reproducible platform enabling the adequate implementation of end-stage preclinical screening of new drugs targeting alpha-synuclein.